Ibrutinib versus temsirolimus: 3-year follow-up of patients with previously treated mantle cell lymphoma from the phase 3, international, randomized, open-label RAY study - Rule, Simon; Witzens-Harig, Mathias (Leukemia, 2018)
Brief Communication
Gesehen am 30.04.2019